Trihoney reduces lipid peroxidation and enhances antioxidant enzyme activities in hypercholesterolaemic atherosclerotic rabbits - Hamad Alfarisi, Hamad Abdulsalam; Ibrahim, Muhammad; Hamad Mohamed, Zenab; Hamdan, Asmah Hanim; Che Mohamad, Che Anuar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2020)
Oxidative stress and reactive oxygen species (ROS) constitute a major pathogenic mechanism for the development of atherosclerosis. In the present work, the antioxidant potential of Trihoney was investigated in hypercholesterolaemic rabbits. Thirty-six male New Zealand white (NZW) rabbits were grouped into: normal diet (C), normal diet with 0.6 g/kg/day of Trihoney (C+H), 1% cholesterol diet (HCD), 1% cholesterol diet with 0.3 g/kg/day of Trihoney (HCD+H1), 1% cholesterol diet with 0.6 g/kg/day of Trihoney (HCD+H2), and 1% cholesterol diet with 2 mg/kg/day of atorvastatin (HCD+At.). Animals were sacrificed following 12 weeks of treatment, and their serum was analysed for oxidised-low density lipoprotein (Ox-LDL). Serum and aortic tissue homogenate were assayed for superoxide dismutase (SOD), glutathione peroxidase (GPx), and malondialdehyde (MDA). Hypercholesterolemia caused a significant (p < 0.05) elevation in serum Ox-LDL and a significant (p < 0.05) reduction of antioxidant enzyme activities in serum of the HCD group. Trihoney induced a significant (p < 0.05) increase in antioxidant enzyme activities in serum as compared to the HCD group. The high cholesterol diet suppressed both antioxidant enzymes in aortic homogenate. Trihoney significantly (p < 0.05) enhanced both antioxidant enzymes in aortic homogenate. Hypercholesterolemia induced a significant (p < 0.05) elevation of serum lipid peroxidation in the HCD group. Trihoney caused a significant (p < 0.05) reduction of lipid peroxidation in aortic homogenate. These results demonstrated that Trihoney has the potential to ameliorate oxidative stress systemically, as well as locally in the atherosclerotic aorta.